Unraveling a dilemma in healthcare projects:Is it about Quality Improvement or Research? - Soli, Silvana; Appeceix, Jennifer S.; Senillosa, Mónica; Perman, Gastón; Grande Ratti, María F. (Revista del Hospital Italiano de Buenos Aires, 2026)
In health sciences, differentiating between a research project and a management or quality project can be confusing, as both employ similar methods such as data collection, statistical analysis, and reporting of results. However, research seeks to generate generalizable knowledge and requires ethical approval, while quality improvement focuses on optimizing internal processes, with no intention of applying the findings outside the local setting. The confusion arises when a management/quality project uses methodologies specific to clinical research, or seeks to be communicated or published. The key lies in the purpose: if it seeks to answer a scientific question applicable beyond the immediate context, it is research; if the objective is to solve an operational problem in an institution, it is improvement. Consulting the institutional review board when in doubt is a good practice to ensure regulatory and ethical compliance.